Discussion on "Sequential detection/isolation of abrupt changes" by Igor V. Nikiforov. Issue 3 (2nd July 2016) - Liu, Kun; Mei, Yajun
ABSTRACT: In this interesting article, Professor Nikiforov reviewed the current state of quickest change detection/isolation problem. In our discussion of his article we focus on the concerns and the opportunities of the subfield of quickest change detection or, more generally, sequential methodologies, in the modern information age.